4 - Les femmes chefs de famille à Dakar: by Codou Bop - Codou Bop (Africa Development, 1995)
This article is a synthesis of social works on, including the author's experience of, the social and economic changes in the urban families and peripheral districts of Dakar (Senegal), with a particular emphasis on women-headed households. The author reviews the characteristics of the such families and analyses the impact of the overall economic situation on their profiles. The author came up with the concept of 'women as breadwinners' with a precarious social status, despite the existing solidarity networks.